EVALUATION OF THE EFFECTIVENESS OF DRY EXTRACT OF SAKHALIN WILLOW SHOOTS ON IRON HEMOSTASIS IN EXPERIMENTAL THROMBOPHLEBITIS - Maloshtan, L.M.; Hrubnyk, I.M.; Iakovlieva, L.V.; Chorna, O.V. (World of Medicine and Biology, 2024)
The dry extract of the shoots of the Sakhalin willow was taken as the object of the study, as a therapeutic and preventive agent. The experiment was conducted on rabbits. Experimental thrombophlebitis was induced by injecting an intravenous solution of 2 % Lugol in a dose of 0.1 ml into the marginal vein of the ear. To assess the state of antioxidant protection in blood serum and the therapeutic effect of the dry extract of Sakhalin willow shoots, the following indicators were selected: the level of transferrin saturation, the concentration of iron in the blood, the total iron-binding capacity of the blood serum, the unsaturated iron-binding capacity of the serum. In the group of animals that received dry extract of Sakhalin willow shoots in a prophylactic-therapeutic regimen, a decrease in the concentration of iron in the blood serum was observed, and at the same time, an increase in the total iron-binding capacity of the blood serum and the unsaturated iron-binding capacity of the serum. It was proved that the extract of Sakhalin willow shoots affected the indicators of antioxidant protection against the background of experimental thrombophlebitis in rabbits. This action is related to the metal-chelating properties of the flavonoids identified in the extract.
Keywords: Sakhalin willow; thrombophlebitis; iron hemostasis; antioxidant protection; metal-chelating activity